Help-Seekers in an Early Detection of Psychosis Service: The Non-cases - Lindhardt, Line; Lindhardt, Morten; Haahr, Ulrik Helt; Hastrup, Lene Halling; Simonsen, Erik; Nordgaard, Julie (Frontiers in Psychiatry, 2021)
Purpose Enhancing early help-seeking is important for early intervention in psychosis. However, knowledge is limited about those help-seekers who are not initially found to have psychotic symptoms when assessed in services aiming at psychosis detection and thus, deemed ineligible for early intervention of psychosis programs. We aimed to examine clinical diagnostic and socioeconomic pathways of help-seekers accessing an early detection of psychosis service with referral-free access. Specific focus was on the help-seekers initially assessed not to have psychotic symptoms, considered the non-cases, and to examine potential differences and similarities between non-cases, and the cases (i.e. those initially assessed to have psychotic symptoms). Methods We followed 450 help-seekers assessed by a free-of-referral early detection of psychosis team in national registers for up to 4 years. We examined clinical diagnoses and status of not in education, employment or training (NEET) before and after contact with the team. Results Of the non-cases, 46% were referred to mental health services by the early detection of psychosis team for evaluation of other mental disorders, and 15% of these were subsequently diagnosed with a non-affective psychotic disorder during follow-up of 12–52 months. Prior to current help-seeking, 39% (n=174) of the help-seekers had had contact with other mental health services. Nearly a quarter of help-seekers were NEETs at the time of assessment; the number increased during follow-up, both for cases and non-cases. Of the cases, 58% were subsequently clinically diagnosed by mental health services. Those seeking help who had no previous contact with mental health services were more frequently diagnosed with a non-affective psychotic disorder during follow-up (p=0.05). Conclusion Referral-free services to promote early detection of psychosis seem a valuable add-on to established pathways, allowing early intervention in psychosis. Our results point to an unmet mental health service need among non-cases; overall in our sample, independent of case status, social functioning was markedly affected. Our results have implications for future focus in early detection of psychosis. Offering intervention to non-cases within the service has the potential to be cost-effective, e.g., if a timely and targeted intervention reduces repeated contacts in other mental health services and social services.